A new species of the genus Asobara Foerster (Hymenoptera: Braconidae) parasitic on Zeugodacus cucurbitae (Coquillett) (Diptera: Tephritidae) infesting tomato in India - Gupta, Ankita; David, K. J. (Zootaxa, 2021)
Asobara jenningsi Gupta sp. nov., a new parasitoid of the braconid genus, is described and illustrated from Karnataka, India. The new species is compared with all the possible closely allied species from the Oriental region.